Electronically Conductive Vanadate Glasses for Resistive Plate Chamber Particle Detectors. (5th February 2015) - Johnson, Nicole; Wehr, Gene; Hoar, Eric; Xian, Siyu; Akgun, Ugur; Feller, Steve; Affatigato, Mario; Repond, Jose; Xia, Lei; Bilki, Burak; Onel, Yasar
Abstract : Particle detectors are constantly being built and refitted with new technology to improve the spatial resolution, radiation hardness, and speed at which the detector can capture particle events. One of the most crucial components of a modern collider experiment is the hadron calorimeter. One of the proposed improvements on future hadron calorimeters is to utilize resistive plate chambers (RPCs). They provide the spatial and energy resolution as well as could provide speed and radiation hardness. RPCs depend on manufacturing electrically conductive glasses that are mechanically strong, durable, radiation resistant, and not ionically conductive. To achieve such requirements, vanadate glasses were developed as alternatives to current prototypes which use soda lime silicate glasses. The conductivity, oxidation states of vanadium, radiation hardness, as well as the prototype performance, were tested on vanadate glasses. The prototype tests show that using 0.40ZnO−0.40TeO2 −0.20V2 O5 can improve the RPC detector rate up to 100 times.